Political Parties in the Digital Age. - Lachapelle, Guy (De Gruyter textbook., 2015)
The Internet and "social media" may initially have been understood as just one more instrument politicians could employ to manage without political parties. However, these media cannot be reduced to being a tool available solely to politicians. The electronic media make reinforcement of the "glocalization" of the public/political sphere, a process already set in motion with the advent of television, and they can develop the trend even further.